Analisis Trend Financial Restatement: Studi Bibliometrik dengan VOSviewer - Muhamad Wahyu Hidayatulloh; Ahmad Fahrudin Alamsyah; Sri Andriani (Journal of Trends Economics and Accounting Research, 2024)
This study aims to determine the mapping of research on the trend of financial restatement using a quantitative approach in the VOSviewer bibliometric study. The data analysis technique used is to map the results of VOSviewer's bibliometric visualization around the trend of financial re-presentation based on the number of clusters and items. The results of the Network Visualization of Co-occurrence show that: based on the mapping of the VOSviewer bibliometric study, the results of the network visualization around the trend of financial re-presentation are divided into 5 clusters and 216 topic items. Meanwhile, based on overlay visualization and density visualization in 2020-2022 centered on Financial Restatement, it means that many studies have been conducted by other researchers.